GEREJA, ERA DIGITAL DAN LAYANAN ROHANI: MEMBACA TANTANGAN, MENIMBANG PELUANG - Rikardus Jehaut & Fredrikus Djelahu Maigahoaku (Jurnal Alternatif Wacana Ilmiah Interkultural, 2022)
The digital era with its rapid and inevitable development today presents a simultaneous challenge and opportunity for the Catholic Church in relation to spiritual services to the faithful. This document study aims to describe, explore and analyze it by using the authoritative documents as the primary data and the various articles and online news as the secondary data. This study shows that the ordinary spiritual services provided by the Church which some of them presuppose direct interactive-communicative participation and encounters as a condition for appropriateness and for validity is challenged by the rapid development of technology that supports various activities, mobility and flexibility. On the other hand, it also brings a golden opportunity. This study concludes that the Catholic Church must develop a digital era spiritual services for the faithful by turning the challenges into opportunities while maintaining a spiritual service that requires physical presence for it appropriateness and validity.